A glimpse on the occurrence of wilting in acacia mangium plantation in Sabah - F.E. Anthony; M. Sudin; Mandy Maid; Yong, Wilson Thau Lym; N.M. Yunus (Faculty of Science and Natural Resources, 2020)
Since late 1980s Acacia mangium has been the main plantation species in Sabah, Malaysia due to its impressive growth rate, less site-selectivity and suitability for structural utilities including chip and paper, hence assuring a promising return. However, as common to monoculture, it is subjected to the attack by diseases including vascular wilt, conservatively attributed to the fungi, Ceratocystis sp., which has caused an alarming rate of mortality in SAFODA’s Ulu Kukut Plantation in the northern region of the state. By employing both field and green house procedures, the study is meant to determine the incidence and severity of the symptom, to evaluate the effect of pruning practices and to investigate the pathogenicity of the isolates against healthy hosts in controlled environment. The findings would serve as valuable input for the management strategies by SAFODA in various ways for optimal production from the species.